Absolute Centroid Location of Submarine Earthquakes from 3D Waveform Modeling of Water Reverberations. Issue 5 (14th May 2020) - Castellanos, Jorge C.; Zhan, Zhongwen; Wu, Wenbo
Abstract: Oceanic transform faults (OTFs) represent an attractive tectonic environment to investigate how slip is accommodated within the crust. However, as most of these fault systems grow in the deep ocean, where few local seismic observations are available, characterizing their earthquake behavior is complicated and remains a formidable challenge. Here we present a novel approach for retrieving precise centroid locations of submarine earthquakes that is based on the modeling of water phases in teleseismic records. Using a hybrid method for simulating far‐field body waves with 3D source‐side structures, we demonstrate that the scattered energy generated by the continuous bounces of an earthquake's P‐wave trapped in the ocean is modelable and carries information about its source location. As a case study, we use a realistic bathymetry model of the Gofar transform fault on the East Pacific Rise and simulate the seismic wavefield at US Array stations for four of its moderate‐sized (Mw5.0+) earthquakes. Our modeling results show that water phases are sensitive to a ∼5 km change in the earthquake's horizontal location and that a remarkable agreement between observed and synthetic water phases is achieved when the location of an event is close to its true one. We then relocate three of these events by systematically computing their water phases in candidate locations until a satisfactory waveform fit is achieved. This analysis technique paves a new route for studying earthquake source properties in isolated marine environments and serves as a mean to investigate the seismic behavior of OTFs on a global scale. Key Points: Seismic recordings of submarine earthquakes show strong arrivals that are caused by the reverberations of their P‐wave energy in the ocean 3D hybrid simulations can be used to model water reverberations and extract valuable information about the earthquake's centroid location Resolution of current global bathymetry models is sufficient to model water reverberations in any oceanic fault system in the world